New Product Development and Innovation for Growth and Profitability of Companies - Gebre-Georges, Fikreselasie Solomon (My University, 2011)
The objective of this thesis is to provide a model for company’s capability and growth of profitability in new product development and innovative technological development. These developments help companies to enhance and investigate the product development activities strategic planning and to build innovative organizational structure. As well as makes advances in applying a dynamic capability approach to innovative competence development and technological competence in NPD to create a value and to achieve in sustainable competitive advantage. This research discovered that the importance and challenges of NPD innovation. Most companies are creating innovation based on collaborative efforts of multiple departments than using their own organization. Also companies may choose between different kinds of organizational structure for the NPD process such as functional or cross functional approach particularly explorative and exploitative activities. In addition firms are required to combine operational effectiveness and strategic flexibility in order to fulfil today’s customers’ requirements in terms of function, time, price and quantity. Several technologies demonstrate increasing returns to adoption, this means the more technology is adopted the more valuable they come if this technology converted in to a convenient product, process or service. Successes begin by thinking about the opportunity to fulfil a real customer who needs a job done and to build a plan how the firm will fulfil that need at a profit. Also to compare the new model with the current model to see how much need to change it to capture the opportunity. However success is not starts by thinking about only business models at all. Many companies were working on finding ways to make a possibility to achieve in sustainable competitive advantage and to create a value for their customers. However this is not always easy task it needs the integration of various methods that provided in this research.
Keywords: New product development; Continues innovation process; Organizational structure; Technology integration; The capability of firm; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|